Improving past sea surface temperature reconstructions from the Southern Hemisphere oceans using planktonic foraminiferal census data. (27th June 2016) - Haddam, N. A.; Michel, E.; Siani, G.; Cortese, G.; Bostock, H. C.; Duprat, J. M.; Isguder, G.
Abstract: We present an improved database of planktonic foraminiferal census counts from the Southern Hemisphere oceans (SHO) from 15°S to 64°S. The SHO database combines three existing databases. Using this SHO database, we investigated dissolution biases that might affect faunal census counts. We suggest a depth/ Δ C O 3 2 − threshold of 3800 m/ Δ C O 3 2 − = −10 to −5 µmol/kg for the Pacific and Indian Oceans and 4000 m/ Δ C O 3 2 − = 0 to 10 µmol/kg for the Atlantic Ocean, under which core‐top assemblages can be affected by dissolution and are less reliable for paleo‐sea surface temperature (SST) reconstructions. We removed all core tops beyond these thresholds from the SHO database. This database has 598 core tops and is able to reconstruct past SST variations from 2° to 25.5°C, with a root mean square error of 1.00°C, for annual temperatures. To inspect how dissolution affects SST reconstruction quality, we tested the data base with two "leave‐one‐out" tests, with and without the deep core tops. We used this database to reconstruct summer SST (SSST) over the last 20 ka, using the Modern Analog Technique method, on the Southeast Pacific core MD07‐3100. This was compared to the SSST reconstructed using the three databases used to compile the SHO database, thus showing that the reconstruction using the SHO database is more reliable, as its dissimilarity values are the lowest. The most important aspect here is the importance of a bias‐free, geographic‐rich database. We leave this data set open‐ended to future additions; the new core tops must be carefully selected, with their chronological frameworks, and evidence of dissolution assessed. Key Points: A new Southern Hemisphere planktonic foraminifera database compilation for SST Improved precision of paleo‐SST reconstructions by reducing dissolution biases in SHO core tops Improved SST reconstructed for core MD07‐3100 using SHO database with the modern analog technique